Odpowiedzi

2009-10-11T12:12:05+02:00
(x+1)(x-1) + (x+2)(x-2) - (x+3)(x-3)=x^2-1+x^2-4-x^2+9=
x^2+4 teraz podstawiamy
x^2+4=(V3)^2+4=3+4=7

(1-2x)(1+2x) + (1-3x) - (1-4x)(4x+1)=1-4x^2+1-3x-1+16x^2=14x^2-3x+1
teraz podstawiamy
x^2-3x+1=(V5)^2-3V5+1=5-3V5+1=-3V5+6

V-pierwiastek
^do potęgi
2009-10-11T12:16:23+02:00

a) (x+1)(x-1) + (x+2)(x-2) - (x+3)(x-3)=
=x²-x+x-1+x²-2x+2x-4-x²+3x-3x+9=
=x²+4

(√3)²+4=3+4=7


b)(1-2x)(1+2x) + (1-3x) - (1-4x)(4x+1)=
=1+2x-2x-4x²+1-3x-4x-1+16x+4x²=
=1+9x

1+9√5
2009-10-11T12:19:22+02:00
(x+1)(x-1) + (x+2)(x-2) - (x+3)(x-3) dla x=pierwiastek 3

(x+1)(x-1) + (x+2)(x-2) - (x+3)(x-3)=

=x²-1+ x²-4 - (x²-9) =
=x²+4 teraz
√3²+4=3+4=7

(1-2x)(1+2x) + (1-3x) - (1-4x)(4x+1) dla x pierwiastek 5

(1-2x)(1+2x) + (1-3x) - (1-4x)(4x+1) =

=1-4x² + 1-3x- (1-16x²)=
=12x²-3x+1
tearz
12√5²-3√5+1=12×5-3√5+1=61-3√5